Business - Jennings, Marianne Moody (Thomson/West, 2006)
BUSINESS: ITS LEGAL, ETHICAL AND GLOBAL ENVIRONMENT offers the most integrated approach to Legal Environment on the market -- thoroughly exploring the intersection of law, business strategy, and ethics illustrated by emphasizing applications (nearly 300 real-world applications throughout the text). In addition to a providing very thorough coverage of the law, the book consistently applies legal concepts within a business context through a wealth of pedagogical devices, demonstrating to students on nearly every page the clear relevance of the material to issues they will face in the real world. This text fulfills current curricular and AACSB accrediting standards